PELAYANAN ADMINISTRASI KEPENDUDUKAN DALAM PENYELENGGARAAN E-KTP DI KECAMATAN TAMPAN KOTA PEKANBARU - Ismayani "; Zulkarnaini " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Law Number 25 of 2009 concerning Public Services, as a reference policy for all public service agencies in providing quality services. Providers of quality public services by the government to the community have a very important role in determining national success and development on an ongoing basis. The community will feel satisfaction if they receive good and professional services from service providers. In addition, human resources (HR) are one of the determinants of success in providing public services. The problem of making e-KTP in Tampan Subdistrict, Pekanbaru City, namely: 1. HR owned by the government pekanbaru in the management of e-KTP that is not optimal. 2 Facilities and Infrastructure. 3 SOP has not been implemented properly in Tampan District, Pekanbaru City. The purpose of this study was to analyze the implementation of population administration services in the implementation of the e-KTP of the Charming City Head Office in Pekanbaru City and to find out the factors that influence Population Administration Services in the Implementation of e-KTP of the Charming City Head Office in Pekanbaru City. The location of this research is the research conducted in Pekanbaru City. The related research locations are in the Camatan Tampan Office of Pekanbaru City. This study uses the theory of Pasuraman (Makmur & Thoha, 2017) which consists of: Tangible, Reability, Responsiveness, Assurance, Empathy. The research method used is qualitative with a phenomenological approach with data collection techniques namely interviews, observation, and documentation. The results of this study indicate that the public response regarding the service of making e-KTP in the UPTD of Tampan District, Pekanbaru City is categorized as not unable to fulfill service needs according to the prescribed procedures. In addition, employees who work in the UPTD of Tampan Subdistrict, Pekanbaru City have not been able to provide maximum service, lack of infrastructure, lack of human resources that facilitate servants to the community.  Keywords: Service, Population Administration, Implementation of e-KTP.